Estimating cardiac output from coronary CT angiography: an individualized compartment model in comparison to the Stewart–Hamilton method - Leiknes, Jon Bjarne; Hiorth, Aksel; Havnen, Jorunn; Greve, Ole Jacob; Kurz, Kathinka Dæhli; Larsen, Alf Inge (Frontiers in Cardiovascular Medicine, 2023)
Background: Attenuation correlates with the concentration of contrast medium [CM] in the arteries. The cardiac output [CO] affects the concentration of contrast medium in the circulatory system; therefore, the Time Density Curve [TDC] is affected by the CO. Thus, it is possible to estimate CO using TDC from test-bolus images acquired in computed tomography [CT]. Herein, we compare two methods to estimate CO; an individualized mathematical compartment model, integrating patient, contrast and scanning factors with TDC, and the Stewart-Hamilton method based on the area under the curve of the TDC. Materials and methods: Attenuation in the aorta was measured during test-bolus in 40 consecutive patients with a clinical indication for coronary CT angiography [CCTA]. Each participant underwent cardiac magnetic resonance imaging following CCTA, as a method of validating estimated CO. The individual compartment model used TDC in conjunction with scanning and patient specific parameters to estimate concentration of CM over time and estimate CO. This was compared to CO calculated from the area under the curve using the Stewart-Hamilton method. Results: Correlation between estimated and measured CO with our individualized compartment model (r=0.66, p<0.01), and the Stewart-Hamilton method (r=0.57, p<0.01) were both moderately correlated. Body Surface Area [BSA] and Time to Peak [TTP] affected the accuracy of our model. Lower BSA resulted in overestimation, and lower TTP resulted in underestimation of CO, respectively. There was no gender specific difference in our model's accuracy, when correcting for BSA. The Stewart-Hamilton method performed better with a more complete TDC, whereas the compartment model performed better overall with a partial TDC. Conclusion: The TDC acquired in CCTA allows for estimation of CO. The Stewart-Hamilton method and our mathematical compartment model both show moderate correlation when applied to our data, though each method has its strengths and limitations. If the majority of the TDC is known, the Stewart-Hamilton method may be more reliable, but an individual compartment model seems to be preferable when there are insufficient data points in the TDC. Regardless, both methods show potential to increase the diagnostic information acquired from a CCTA, which is increasingly recommended in clinical guidelines.